Kewajiban Menuntut Ilmu dalam Islam - Wikhdatun Khasanah (Jurnal Riset Agama, 2021)
The purpose of this paper is to discuss the hadith about the obligation to study. This research method uses a qualitative type through literature study and content analysis. The results and discussion of this study include a general view of the obligation to study, hadith about the obligation to study, and how to study ethics. This study concludes that the hadith regarding the obligation to seek knowledge explains that seeking knowledge is one of the most important parts of human life, without knowledge humans will not be able to develop. Seeking knowledge is also considered as a starting point in growing awareness in attitude. Seeking knowledge is obligatory for every Muslim male and female Muslim. When Allah has sent down an obligatory command on something, then we must obey it.